Going to the zoo in Hawaiʻi - Ebie, Mora.; Murakami, Jon J. (Honolulu, Hawaii : Mutual Pub., 2006)
A family walks through Waikiki to visit a Hawaiian zoo, where they see many exotic animals.
Keywords: Honolulu Zoo -- Juvenile fiction; Honolulu Zoo -- Fiction; Zoo animals -- Fiction; Hawaii -- Fiction